FLIGHT DYNAMICS MODEL OF ONE CLASS OF AIRCRAFT WITH A VIEW OF ELASTIC CONSTRUCTION - A. I. Nikitin (Научный вестник МГТУ ГА)
It remains urgent problem of damping of elastic vibrations occurring aircraft structure means the automatic control systems on board. In solving this problem the aircraft elastic model is the basis for the synthesis of control laws and analysis of closed-loop system "control object - the regulator." In general, the problem of mathematical modeling of flight dynamics of the elastic aircraft breaks for at least another two objectives, one of which - direct simulation of the behavior of elastic aircraft defined interacting forces, and the other - the account of the changes operating aerogidrodynamic forces and moments caused by the deformation elastic aircraft and work control systems. This paper discusses the theoretical basis of the approach to the solution of this problem, based on the replacement of the actual design of aircraft by equivalent circuit and its implementation for the missiles, the most simple in terms of schematic, class of aircraft. At the same time accounting for changes in aerodynamic forces and moments caused by the elastic deformation of the aircraft, it was performed by help of stationary hypothesis